Food security and welfare of red rice farmers on dry land in Ponjong district, Gunungkidul regency - Rahayu, Lestari; Wijaya, Oki; Syaputra, Rino; Robani, Anidah (2023)
Cultivating red rice in Gunungkidul Regency s dry lands is seen as a promising means to alleviate poverty, primarily due to its higher market value, which can fulfill the basic needs of farming households, ensure food security, and enhance their overall well-being. This study specifically evaluates the food security and welfare of dryland red rice farmers in the Ponjong District of Gunungkidul Regency. A sample of 200 farmers was selected using Systematic Random Sampling, with a specific emphasis on the Share of Food Expenditure and the Sajogyo Indicator for analysis. The results reveal significant food security disparities; the southern zone has slightly higher food insecurity (HFES 50.6%). To enhance well-being, policy efforts should prioritize boosting red rice income, strengthening food security, and reducing welfare disparities in all zones, as indicated by various analyses, including GSR (Good Service Ratio), FER (Exchange Rate Analysis of Farmer Income), and the Sajogyo indicator. While none of the zones are categorized as prosperous by GSR, FER designates the southern and northern zones as prosperous, and the Sajogyo indicator classifies all zones as moderately viable, with the central zone showing the most potential for improvement.